Introduction of team-based learning (TBL) at Kilimanjaro Christian Medical University College: Experience with the ectoparasites module. (April 2014) - Nyindo, Mramba; Kitau, Jovin; Lisasi, Esther; Kapanda, Gibson; Matowo, Johnston; Francis, Patrick; Bartlett, John
Abstract Background: Contemporary teaching in sub-Saharan African medical schools is largely through didactic and problem-based approaches. These schools face challenges from burgeoning student numbers, severe faculty shortages, faculty without instruction in teaching methods and severe infrastructure inadequacies. Team-based learning (TBL) is a pedagogy which may be attractive because it spares faculty time. TBL was piloted in a module on ectoparasites at the Kilimanjaro Christian Medical University College (KCMU Co.). Methods: TBL orientation began six weeks before starting the module. Students were issued background readings and individual and group readiness assessment tests, followed by module application, discussion and evaluation. At completion, student perceptions of TBL were assessed using a 5-point Likert scale evaluating six domains, with a score of 5 being most favourable. Strength of consensus measures (sCns) was applied. Final examination scores were compiled for 2011 (didactic) and 2012 (TBL). Results: About 158 students participated in the module. The mean student scores across the six domains ranged from 4.2 to 4.5, with a high degree of consensus (range 85–90%). The final examination scores improved between 2011 and 2012. Conclusions: KCMU Co. student perceptions of TBL were very positive, and final exam grades improved. These observations suggest future promise for TBL applications at KCMU Co. and potentially other schools.